An additional gastrojejunostomy may reduce the incidence of moderate and severe delayed gastric emptying after distal segmental duodenectomy for gastrointestinal stromal tumors - Jia, Wei-Wei; Wu, Jian-Hui; Yang, Cui; Liu, Dao-Ning; Wang, Xiao-Peng; Sun, Rong-Ze; Li, Cheng-Peng; Hao, Chun-Yi (World journal of surgical oncology, 2024)
To investigate whether an additional gastrojejunostomy reduces the incidence of delayed gastric emptying (DGE) following a distal segmental duodenectomy for duodenal and proximal jejunal gastrointestinal stromal tumors (GIST). This retrospective review of the GIST database at Peking University Cancer Hospital included 50 patients who underwent distal segmental duodenectomies for primary GIST in the duodenum or proximal jejunum within 20 cm of Treitz’s ligament between January 2008 and December 2023. The patients were divided into two groups: non-bypass (without gastrojejunostomy) and bypass (with gastrojejunostomy and Braun’s jejunojejunostomy). Perioperative characteristics and postoperative complications were analyzed. Among the 50 patients, 27 underwent duodenojejunostomies without gastrojejunostomies and 23 with gastrojejunostomies and Braun’s jejunojejunostomies. The incidence of grade B-C DGE was significantly lower in the bypass group (43.5% vs. 74.1%, p = 0.028). In addition, non-bypass surgery was an independent risk factor for increased grade B-C DGE (OR 3.67, 95% CI 1.07-12.64, p = 0.039). The bypass group showed a trend towards a shorter postoperative hospital stay (median: 14 days, range: 10-56) compared to the non-bypass group (median: 28 days, range: 6-75), but this difference did not reach statistical significance (p = 0.070). Operative time (min) was significantly longer in the multi-visceral resection group (381.0 ± 108.8 vs. 227.3 ± 87.6, p < 0.001), for tumors ≥ 6.3 cm compared to < 6.3 cm (337.0 ± 116.4 vs. 228.3 ± 99.8, p = 0.002), and in patients with positive preoperative symptoms versus asymptomatic patients (319.9 ± 118.0 vs. 210.2 ± 90.3, p = 0.031). The addition of gastrojejunostomy and Braun’s jejunojejunostomy in distal segmental duodenectomy can reduce the incidence of grade B-C DGE, potentially facilitating timely adjuvant imatinib therapy. Future multicenter studies are needed to confirm these findings.